Stenting versus non-stenting following uncomplicated ureteroscopic lithotripsy: comparsion and evaluation of symptoms - Savić, Slaviša Č; Vukotić, Vinka; Lazić, Miodrag; Savić, Nataša (Vojnosanitetski pregled, 2017)
Background/Aim. Currently, ureterorenoscopic (URS) stone fragmentation and removal is the treatment of choice for managing ureteral stones, especially mid and distal ones and is advocated as initial management of ureteric stones. The aim of this work was to evaluate the symptoms, necessity, potential benefits and adverse effects of ureteral stent placement after uncomplicated ureteroscopic lithotripsy. Methods. This retrospective-prospective study evaluated a total of 125 patients who had underwent ureteroscopic lithotripsy (URSL). The patients were divided into two groups: stented (59 patients) and unstented (controls, 66 patients). The outcomes measured and compared between the two groups included: stone free rate, postoperative patient pain validated by scale, lower urinary tract symptoms (LUTS), the need for unplanned hospital care, stent related complications, and functional recovery in the form return to normal physical activities. Results. A successful outcome, defined as being stone-free after 12 weeks, was achieved in all 125 (100%) patients. The stone-free rate showed no significant differences between the two groups. LUTS was a frequent complaint in the stented group, with statistically significant difference in the domain of frequency/urgency (p = 0.0314). There was a statistically significant difference between the groups in the mean operative time and mean hospitalization time, mean pain visual analog scale (VAS) score and in the use of non-narcotic analgesic. On the day of the surgery and until postoperative day 3 (POD 3) and postoperative day 5 (POD 5), the pain score was much higher among stented patients than among the controls (p = 0.0001) and non-narcotic analgesic use (p = 0.001) was frequently required in the stented group. Conclusion. Routine placement of ureteral stent after URSL is not mandatory and may be associated with stent side effects. Uncomplicated URSL is safe without stent placement after the treatment.
Keywords: ureteroscopy; lithotripsy; stents; lower urinary tract symptoms; comparative study